Analysis of the english language learning system through levels in the Unidad Educativa Experimental Bilingüe Rosa de Jesús Cordero - Moscoso, María Elena; Mosquera, Ana
This work is an analysis of the English Language Learning System through Levels (ELLS through Levels) in the Unidad Educativa Experimental Bilingüe Rosa de Jesús Cordero. We have considered some important aspects such as the criteria and the ways to place the students according to their language level. Our purpose is to explain how the students are placed in the different levels in this institution. This study is based on the pedagogical theories of the Constructivism, Meaningful Learning, and the Creative Construction Theory. The Constructivism Theory recognizes the uniqueness and complexity of the learner further more encourages it as an integral part of the learning process. The Creative Construction Theory states that learners are thought to construct the internal representations of the language that they are learning. This study presents the teachers and students´ opinions about the English language Learning System through Levels taking into account the advantages and disadvantages of the ELLS through Levels in the classroom´ environment and the teaching-learning process. For this reason, we have analyzed two courses, Segundo de Bachillerato High Level and Low Level of the Unidad Educativa Rosa de Jesús Cordero. We present and contrast the grades, books, and methodologies used with these students. Finally, we purpose some recommendations to improve the results in the English Language Learning System through Levels in the Unidad Educativa Experimental Bilingüe Rosa de Jesús Cordero